'Blister free' membranes are targeted at the dairy-processing industry. Issue 3 (March 2017) - Unknown
Abstract : For the last two years GEA Group Aktiengesellschaft in the USA has been working closely with General Electric (GE) to support the latter's membrane manufacturing technology to better meet their joint customers' needs, in particular those operating in the dairy-processing sector.